Enantioselective Synthesis of a (1R,5R,9R)-2-Azabicyclo[3.3.1]nonane-9-carboxylic Acid with an Embedded Morphan Motif: A Multipurpose Product - Garrido, Narciso M.; Nieto, Carlos T.; Díez, David (Synlett, 2013)
A convenient asymmetric synthesis of (1R,5R,9R)-2-azabicyclo[3.3.1]nonane-9-carboxylic acid is described, starting from (2E,7E)-dimethyl nonadienedioate. The route involves a stereoselective domino Michael–Dieckman process that furnishes a 1,2,3-trisubstituted cyclohexane derivative bearing three adjacent stereocenters with full stereochemical control. A subsequent chemoselective transformation of one of the side-chain ester groups allows an effective second cyclization leading to the morphan motif. The versatility of this novel amino acid for the generation of molecular complexity was tested by elaborating a tripeptide in homogeneous phase.
Keywords: β-amino acids; asymmetric synthesis; Michael addition; morphan; GABA uptake inhibitors